Tipificaciones y sinónimos nuevos en Echinodorus Engelm. y Sagittaria L. (Alismataceae) de la Flora del Paraguay - Samuli Lehtonen; Lorenzo Ramella (CONSERVATOIRE ET JARDIN BOTANIQUES VILLE GENEVE, 2022)
Abstract
Lehtonen, S. & L. Ramella (2017). Typifications and new synonyms in Echinodorus Engelm. and Sagittaria L. (Alismataceae) of the Flora of Paraguay. Candollea 72: 405–407. In Spanish, English and Spanish abstracts. DOI: http://dx.doi.org/10.15553/c2017v722a17
The lectotype specimen of Echinodorus longipetalus Micheli is designated acording to the rules, correcting a prior but erroneous lectotypification. Four infraspecific names in Sagittaria L. are formally treated as synonyms, remaining one dubious name. Sagittaria montevidensis f. flaviflora Chodat is lectotypified.
Resumen
Lehtonen, S. & L. Ramella (2017). Tipificaciones y sinónimos nuevos en Echinodorus Engelm. y Sagittaria L. (Alismataceae) de la Flora del Paraguay. Candollea 72: 405–407. En español, resúmenes en inglés y español. DOI: http://dx.doi.org/10.15553/c2017v722a17
El lectótipo de Echinodorus longipetalus Micheli está designado aquí de acuerdo a las reglas, rectificando una lectotipificación previa errónea. Se publica formalmente la sinonimia de cuatro nombres infraespecíficos en Sagittaria L., quedando un solo nombre dudoso. Se efectúa la lectotipificación del nombre Sagittaria montevidensis f. flaviflora Chodat.